Urgensi dan Pengembangan Modul Pembelajaran dalam Meningkatkan Kualitas Pembelajaran: Studi Kasus di SMK Arbai Qohhar Ngawi - Muhammad Rofiiqul Umam; Hamam Burhanuddin (Istifkar: Media Transformasi Pendidikan, 2026)
This important effort in its actualization must certainly consider many aspects, including the learning tools used. It is important to understand that in order to realize this innovative educational concept, it is also necessary to pay attention to the use of appropriate and flexible teaching materials. The teaching materials referred to in this case are teaching modules that can help each educator contextualize the material presented to students. The benefits of the modules themselves are actually fundamental, as they open opportunities for students to be able to adjust their learning needs according to their abilities, conceptualize learning styles, and create engaging learning models. The modules also help educators in conceptualizing effective learning processes that can develop the character and potential of students who are not only intelligent but also independent, skilled, and virtuous. This study aims to analyze the definition of a learning module, the basic principles underlying it, the stages of development and implementation of learning modules in the classroom, and the challenges faced. Using a qualitative method with a case study approach, the results of the study indicate that modules have a significant urgency in the teaching and learning process at SMK Arbai Qohhar in Jambangan Village, Paron District, Ngawi Regency. The study results indicate that learning modules play a vital role in creating a structured, independent, and effective learning process. Their implementation enhances student engagement and creativity while facilitating teachers in delivering the material. Despite challenges such as varying teacher competencies and student abilities, modules remain a strategic tool for improving learning quality.